Sampling for biological agents in the environment - Emanuel, Peter; Roos, Jason W.; Niyogi, Kakoli (ASM Press, 2008)
"After September 11 and the anthrax attacks of 2001, the real danger of a large-scale biological terrorist attack was realized. This invaluable volume brings together the latest information on the environmental sampling element of the response to a biological attack. Resulting from a national conference of first responders, scientists, and industry representatives, Sampling for Biological Agents in the Environment presents best practices that will help standardize procedures and technology to properly sample for biological threat agents. The sampling issues, techniques, and equipment are explained for professionals involved in sampling and testing of hazardous materials. Additionally, this volume will help facilitate cooperation and effective communication between various federal, state, and local entities that often have different procedures and methodologies when responding to weapons of mass destruction incidents